Antecedents and consequences of participation in brand communities: a literature review. Issue 4 (July 2018) - Hook, Margurite; Baxter, Stacey; Kulczynski, Alicia
Abstract With hundreds of articles dedicated to investigating brand communities, there is now a need to consolidate the literature. This review addresses the need to reconcile the findings of brand community participation literature through undertaking a literature review. Over 1900 articles were examined, 41 in detail. Findings reveal that three forms of brand community participation have been studied: offline, online, and social-media-based, each uncovering the antecedents and consequences of brand community participation. Antecedents were grouped into five categories (self-related, social-related, information-related, entertainment-related and technology-related) and consequences into three categories (brand-related, brand community-related, and social-related). From the review, several future research directions are uncovered, including 16 specific research questions. By scrutinising the vast literature on brand community participation, and presenting multiple avenues for future research, this review presents findings useful for academics and practitioners alike.